THE EFFECT OF RICE STRAW AMMONIATED FEED AND CONCENTRATE SUPPLEMENTED WITH WARU LEAF MEAL (Hibiscus tiliaceus) ON THE PERFORMANCE AND FEEDING BEHAVIOR OF LOCAL SHEEP - M., FITA; BATA, M.; RAHAYU, S.; SUDRAJAT, A. (Majalah Ilmiah Peternakan, 2024)
The aim of this study to determine interaction between Direct-Fed Microbials (DFM) and Hibiscus leaf meal (HLM) supplementation on local sheep performance and consumption rate of concentrate. Thirty-six males local sheeps aged ± 2 years (28.01 ± 2.61 kg) were fed ammoniated rice-straw supplemented with DFM and concentrate supplemented with HML assigned randomly to nine treatment in an experiment of 3x3 factorial design. The first factor was the use of DFM (P0 = control, P1 = DFMAMS, P2 = DFMRJ) and the second factor was level of HLM (W0 = 0%, W1 = 0.24% and W2 = 0.48% DM concentrate). Concetrate consumption DMI of each sheep was 3% of body weight and ad-libitum JPA. Measured variables were final weight, average daily gain (ADG), feed consumption (FC), fed conversion rasio (FCR) and consumption rate (CR). There was significant interaction (P<0.05) between DFM and HML supplementation on the final weight, FC and CR (P<0.01), while ADG and FCR were not significant- ly interact. DFM supplementation significantly affected (P <0.05) on FCR. The most efficient feed conversion achie- ved in P2 (W0 =8.22 ± 1.19, W1=7.15 ± 0.85 and W2=6, 81 ± 1, 68). There was no interaction on ADG, however ADG tended to increase in W2. The Highest ADG was achieved in P2W2 (0.146 ± 0.03 Kg/day). There was positive correlation between consumption rate and ADG (P<0.01) also consumption rate and final weight (P<0.05). Coeficient correlation of consumption rate and both ADG and final weight were 0, 481 and 0.514, respectively. The use of DFM and HML, especially DFMRJ and level of HLM was 0.48% (P2W2) were able to improve local sheep performance.